Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Telkom Wilayah Meruya Jakarta Barat: The Influence of Work Motivation and Work Environment on Employee Performance of PT Telkom Meruya Region, West Jakarta - Ifaristi (Jurnal Mnajemen | Ekonomi | Akuntansi, 2024)
- Performance refers to employee work performance measured against standards or criteria that have been set by the organization, set by the organization. The purpose of this study was to determine the effect of motivation and work environment on the performance of employees of PT Telkom Meruya Region, West Jakarta. The data used is quantitative using primary data through distributing questionnaires to employees of PT Telkom Meruya Region, West Jakarta. The population of this study amounted to 50 respondents using non-probability sampling method using saturated samples. The data that has been collected is then analyzed using SPSS 15.0. The results showed the influence of Motivation and Work Environment on Employee Performance seen from the F value of 20,423 which means F count> F table (20,423> 3.19) and significant at 0.000 <0.05, it can be said that the Motivation and Work Environment variables simultaneously have a positive and significant effect on the Performance of Employees of PT Telkom Indonesia Meruya Region, West Jakarta.